The Impact of Natural Content, Knowledge of Halal and Green Food, and Religiosity on Product Awareness toward Purchase Intention - Putri, Evi Oktaviana Putri B1024131005 (Jurnal Manajemen Update, 2018)
This research aimed to determine the impact of natural content, knowledge of halal and green foods and religiosity toward purchse intention through awareness as mediator variable and Tropicana Slim Beras Merah Organik product in Pontianak as the research object. People nowadays are more concern and careful when choose a food. They are consider about halal but nowadays more consider about food that has halal and green logo. This research is quantitavive serves to test the hypothesis proposed in the research and answered the problem in the research. The sample of this research is muslim in Pontianak age â‰¥ 17 years old, who has knowledge about halal and green. The data are obtained by using questionnaire. This reseacrh use random sampling, which total sample is 100, and using SmartPLS 3.2.7 software to analyze the data. The hypothesis of this research is H1: Natural content has positive impact toward awareness, H2: Knowledge of halal and green foods has positive impact toward awareness, H3: Religiosity has positive impact toward awareness, and H4: Awareness has positive impact toward purchase intention. The result of this research shows that all of the hypothesis are accepted.Keywords : Natural Content, Knowledge of Halal and Green Foods, Religiosity, Awareness, Purchase Intention